Orientation and Contrast Tuning Properties and Temporal Flicker Fusion Characteristics of Primate Superior Colliculus Neurons - Chen, Chih-Yang; Hafed, Ziad M. (Frontiers in Neural Circuits, 2018)
The primate superior colliculus is traditionally studied from the perspectives of gaze control, target selection, and selective attention. However, this structure is also visually responsive, and it is the primary visual structure in several species. Thus, understanding the visual tuning properties of the primate superior colliculus is important, especially given that the superior colliculus is part of an alternative visual pathway running in parallel to the predominant geniculo-cortical pathway. In recent previous studies, we have characterized receptive field organization and spatial frequency tuning properties in the primate (rhesus macaque) superior colliculus. Here, we explored additional aspects like orientation tuning, putative center-surround interactions, and temporal frequency tuning characteristics of visually-responsive superior colliculus neurons. We found that orientation tuning exists in the primate superior colliculus, but that such tuning is relatively moderate in strength. We also used stimuli of different sizes to explore contrast sensitivity and center-surround interactions. We found that stimulus size within a visual receptive field primarily affects the slope of contrast sensitivity curves without altering maximal firing rate or semi-saturation contrast. Additionally, sustained firing rates, long after stimulus onset, strongly depend on stimulus size, and this is also reflected in local field potentials. This suggests the presence of inhibitory interactions within and around classical receptive fields. Finally, primate superior colliculus neurons exhibit temporal frequency tuning for frequencies lower than 30 Hz, with critical flicker fusion frequencies of less than 20 Hz. These results support the hypothesis that the primate superior colliculus might contribute to visual performance, likely by mediating coarse, but rapid, object detection and identification capabilities for the purpose of facilitating or inhibiting orienting responses. Such mediation may be particularly amplified in blindsight subjects who lose portions of their primary visual cortex and therefore rely on alternative visual pathways including the pathway through the superior colliculus.